2011
DOI: 10.1007/s00425-011-1532-7
|View full text |Cite
|
Sign up to set email alerts
|

OsLIS-L1 encoding a lissencephaly type-1-like protein with WD40 repeats is required for plant height and male gametophyte formation in rice

Abstract: Although a large number of genes encoding the WD40 motif have been identified as being involved in various developmental processes in Arabidopsis, little is known about the function of these genes in rice (Oryza sativa). Here, we report the cloning and functional characterization of a novel rice gene OsLIS-L1 (Lissencephaly type-1-like 1), which is required for normal fertility and the first internode elongation. OsLIS-L1 encodes a lissencephaly type-1-like protein containing the WD40 motif that is required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 61 publications
2
30
0
Order By: Relevance
“…5D-F). Our findings are corroborated by several previous studies reporting nuclear localization of plant WD40-repeat proteins[15,31,32].…”
supporting
confidence: 95%
“…5D-F). Our findings are corroborated by several previous studies reporting nuclear localization of plant WD40-repeat proteins[15,31,32].…”
supporting
confidence: 95%
“…There are three TPL/TPR proteins in rice, namely TPR1(LOC_Os01g15020), TPR2 (LOC_Os08g06480) and TPR3 (LOC_Os03g14980). Among them, TPR2 (also known as ASP1, OsREL2 or OsLIS-L1) has been reported to function in tiller and spikelet development 4042 . As shown in Fig.…”
Section: Interaction Of D53 With Tpr Proteinsmentioning
confidence: 99%
“…S11C). One of the three rice TPRs, TPR2-also termed ABERRANT SPIKELET AND PANICLE1 (ASP1) or Lissencephalytype-1-like1 (OsLIS-L1)-was involved in regulating panicle development (22,23). Yeast two-hybrid assay showed that SNB, OsIDS1, and OsTOE1 interacted with TPR1 and ASP1 in yeast, and a series of protein mutation and truncation assays showed that the EAR C motif of SNB, OsIDS1, and OsTOE1, and the LisH (lissencephaly type I-like homolog) domain of ASP1 were responsible for the interactions (Fig.…”
Section: Effects Of Mir172 and Its Target Genes On The Transition Of mentioning
confidence: 99%